2022
DOI: 10.3389/fsoc.2022.953872
|View full text |Cite
|
Sign up to set email alerts
|

Conducting rapid qualitative interview research during the COVID-19 pandemic—Reflections on methodological choices

Abstract: As the COVID-19 pandemic has shown, setting up studies in time to gather relevant, real-world data enables researchers to capture current views and experiences, focus on practicalities on the ground, and deliver actionable results. Delivering high quality rapid studies in healthcare poses several challenges even in non-emergency situations. There is an expanding literature discussing benefits and challenges of conducting rapid research, yet there are relatively few examples related to methodological dilemmas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…There has been an expansion and advancement of rapid qualitative methods in the context of urgent public health situations ( 8 , 9 , 32 ). In recent years, however, much of the rapid qualitative analysis literature has centered on either rapid analysis as a singular method or rapid approaches in comparison to more “traditional” qualitative methods, leaving a gap in understanding how such rapid and traditional methods might be used together ( 33 ), as we attempted to do with our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an expansion and advancement of rapid qualitative methods in the context of urgent public health situations ( 8 , 9 , 32 ). In recent years, however, much of the rapid qualitative analysis literature has centered on either rapid analysis as a singular method or rapid approaches in comparison to more “traditional” qualitative methods, leaving a gap in understanding how such rapid and traditional methods might be used together ( 33 ), as we attempted to do with our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Forming such diverse qualitative research teams may not be feasible for all DFE projects. To assist in planning DFE research teams, we offer guidance on qualitative rapid analysis team selection based on specific knowledge and skill sets, acknowledging that our guidance is similar to others’ guidance for planning rapid qualitative analysis teams for the broader category of health services evaluations (Wanat et al, 2022). First, although the matrix method is appropriate for use in research teams involving members without prior qualitative research experience (Gale et al, 2013), we found it necessary to have at least one experienced qualitative analyst on the rapid analysis team.…”
Section: Considerations For Qualitative Rapid Analysis In Dfementioning
confidence: 99%
“…Despite being inherent to the process of manual transcription, delays can lead to collected data waning in relevance (9) or, as witnessed in COVID-19 (10), becoming obsolete. Many qualitative teams have sought to mitigate transcription delays by forgoing verbatim transcription in favor of selective transcription or via capturing data in the form of field notes and summaries (11,12). While selective transcription and related techniques can facilitate timely results, these approaches can increase the risk for researcher bias and information loss (13).…”
Section: Introductionmentioning
confidence: 99%